Studi Kelayakan Material Maju Green Economy Blok Jerami Beton Interlock (BERATON) - Dora Melati Nurita Sandi; Zulis Erwanto; Catur Bejo Santoso; Riza Rahimi Bachtiar; Sharfina Nabilah; Fera Fitri Salsabila (I-Com: Indonesian Community Journal, 2025)
Labanasem, Kabat, Banyuwangi Regency consists of 5 hamlets, namely West Krajan, East Krajan, Sukadi, Gotan, and Kawang. The majority of people in Labanasem work as farmers because they have a fairly large agricultural land sector. One of the problems experienced by craftsmen is that most craftsmen have not calculated and analyzed the feasibility of the products they produce. In addition, the group has not been touched by technology and advanced green economy material innovation, therefore with the problem of production costs, it is necessary to optimize production costs with environmentally friendly raw materials and develop more economical product innovations made from rice straw waste that can increase the added economic value of partners. Based on problems, the purpose of community service activities is to empower the Building Materials Craftsmen Group in utilizing rice straw waste for Interlock Concrete Straw Blocks material innovation in Labanasem, Banyuwangi and to analyze the feasibility of interlock concrete straw block material (BERATON). Based on the analysis results, it can be seen that the BERATON product was an innovative and profitable product, the profits obtained by partners in 2024 can reach Rp 39,229,720.00, in 2025 it reaches Rp 48,623,250.00 and in 2026 it reaches Rp 46,982,250.00. The R/C Ratio value was 4.6; the B/C ratio value was 3.6 and the IRR value was 89.34%